The influence of coconut water concentration and duration storage of rootstock to the percentage of budding success and cassava’s (mukibat) growth - Muhammad Indra Iswahyudi; Nini Rahmawati; Mariati Mariati (Jurnal Agroekoteknologi, 2018)
The purpose of the research was to determine the influence of coconut water concentration  and duration storage of rootstock  to the percentage of budding success and cassava’s (mukibat)  growth. The research was conducted at the screen house of Agriculture Faculty USU (± 32m asl) in March-June 2017 using Factorial Randomized Block Design (RAK) repeated 3 (three) times. The first factor was the coconut water concentration  with 4 (four) levels ie without coconut water, 25% coconut water, 50% coconut water and 75% coconut water and second factor of storage duration of rootstock  with 3 (three) treatment levels: 1 (one) week storage, 2 (two) weeks storage, and 3 (three) weeks storage. Parameter observed were percentage of budding success, spinning rate, shoot height, shoot diameter, number of leaves, number of tubers, root wet weight, and root dry weight. The results showed that the coconut water concentration had a significant effect on the success rate of budding, root wet weight, and root dry weight. Where the best coconut water concentration is at 50% coconut water treatment. The longer duration storage of rootstock gives fewer percentage of budding success. The best storage time for rootstock was 1 (one) week storage. The interaction of coconut water concentration and storage duration of rootstock had significant effect on the number of leaves.